FAKTOR-FAKTOR PENGOLAHAN DAN KOMPOSISI BAHAN YANG MEMPENGARUHI CITARASA "OFF FLAVOUR" FORMULA TEMPE - Nelis Imanningsih; Rossi RS Apriyantono; Nunung Nurjanah (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2007)
PROCESSING FACTORS AND INGREDIENTS CONTRIBUTED IN TEMPE FORMULA'S OFF FLAVOUR.Background: Tempe Formula is processed food with tempe as the main ingredient. was previously formulated as infant formula and under five years children formula who have diarrhea problem. In later researches, tempe Fromula was found to be efective to increase nutritional satatus of severe malnourished children, to cure gastrointestinal infection of 6-24 months children, and had benefit to repair dislipldemia in adults and bone reformation of pre and post menopause women. However, this formula had off flavour that limit Its utilization. Methods: The design is laboratory experiment. The type of research is explorative. The panelist is trained panelist.Results: The result shows that off flavour component identified were beany odour, moldy odour, tangy taste and bitter taste. Tempe processing with half boiled of soybean and steam sterilization with traditional starter of mixed innoculum gave the best sensori quality. Less intensity of beany flavour and bitter taste were gained by improving the composition of palm oil and sesame oil with composition 1:1. The additon of mocca and milk flavours also reduced the beany odour of the formula. Conclusion: Improved tempe formula was determined to have higher intensity of sweetness, less intensity of saltyness, bitemess and tangy taste, and less beany, rancid, and moldy odours than original formula.Keywords: tempe formula, off flavour, processing